The Stock Assessment of Crayfish (Astacus leptodactylus Eschscholtz, 1823) in the Keban Dam Lake - Demirol, Ferhat; Yuksel, Fahrettin; Gunduz, Fatih; Beri, Abdulmutalip; Guler, Mehtap; Yildirim, Tacettin; Coban, M. Zulfu (Central Fisheries Research Inst, 2017)
In this study, estimating of catchable stock size, stock density and the amount of annual allowable catches of crayfish population in the Keban Dam Lake was aimed. The Schnabel Method, one of the multiple marking methods, was used to estimate crayfish stock size. The caught crayfish were branded by an electric soldering iron. Mean weight of crayfish that have the minimum allowable length (TL >= 10 cm) was detected as 41 g and catch per unit effort (CPUE) was calculated to be 0.13 crayfish/fyke-net/day both 2012 and 2013. It was determined that the density of crayfish that have greater than (or equal to) total length of 10 cm was 0.91 individual per m(2) for 2012 and 1.07 individual per m(2) for 2013. Accordingly, the biomass of crayfish that have minimum landing size (TL >= 10 cm) was estimated to be 80258 kg for 2012 and 74671 kg for 2013. The total amount of annual allowable catch in the Keban Dam Lake was estimated at 26.7 tons. For individual regions it reached: 7.1 tons for Agin, 6 tons for Keban, 7.7 tons for Cemisgezek and 5.9 tons for Ova fishing regions.
Keywords: Mark-recapture; schnabel method; stock density; CPUE